Viewpoints: how the hippocampus contributes to memory, navigation and cognition - Lisman, John; Buzsáki, György; Eichenbaum, Howard; Nadel, Lynn; Ranganath, Charan; Redish, A David (Nature neuroscience, 2017)
The hippocampus serves a critical function in memory, navigation, and cognition. Nature Neuroscience asked John Lisman to lead a group of researchers in a dialog on shared and distinct viewpoints on the hippocampus.